Model prerequisites for derivation of the Dubinin-Radzhdkevich adsorption equation - A.V. Tvardovskiy (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
To date, a large number of different adsorption and absorption equations have been proposed, describing a variety of equilibrium situations on homogeneous and inhomogeneous surfaces of adsorbents, polymers, micro-, meso- and macroporous adsorbents. However, the most valuable works are those in which attempts are made to build a general theory of adsorption (and absorption). At least the well-known classical adsorption equations should follow from such a general equation as special cases. Thus, in [1] such an equation was proposed and it was shown that the classical Henry, Langmuir, and Brunauer – Emmett – Teller equations with constants having a clear physical meaning follow from it as special cases. Thus, the constant in the Henry equation is determined by the temperature as well as by the specific surface of the adsorbent, the size of the adsorbate molecules, the molar mass of the adsorbate, and the isosteric heat of adsorption (the energy of interaction of the adsorbate molecules with the surface of the adsorbent). In the derived Brunauer – Emmett – Teller partial equation, in contrast to its classical version, a clear dependence of the equation constant on the specific physical characteristics of the adsorption system is provided for the first time. The dependence in question is determined by the concentration of adsorbate molecules in the liquid phase at the temperature under consideration, the concentration of adsorbate molecules during the formation of a dense monolayer on the surface of the adsorbent, and by the energy of interaction of adsorbate molecules with the surface of the adsorbent and the heat of condensation. The presented approach can serve as a basis for modeling a variety of adsorption and absorption phenomena, including adsorption on microporous adsorbents. The Dubinin- Radzhdkevich adsorption equation, which is an empirical one, has been widely applied in adsorption science. In this paper, based on [1], a thermodynamic analysis of the Dubinin-Radushkevich equation is carried out and model prerequisites for the theoretical derivation of this equation in a wide temperature range (up to the critical temperature Tcrit) are identified.